Numerical analyses of the hangingwall at the Kiirunavaara mine - Villegas, Tomas (Luleå tekniska universitet, Geoteknologi, 2008)
The mining method used in the Kiirunavaara Mine induces failure in the hangingwall which caves and subsides by the effect of stress relaxation and gravity. Since the orebody is dipping towards the city of Kiruna, surface disturbances are approaching the town as mining proceeds to a greater depth. The aim of this thesis is to contribute to the understanding of the hangingwall failure process and its relationship with the ground surface subsidence. To achieve this objective two conference papers related to numerical analyses and one journal paper regarding ground surface deformation are compiled. Results from numerical analysis using continuous methods indicate that the first tension cracks are formed by extension strain on the ground surface, followed by shear failure along an almost planar failure surface between the mining level and the tension crack. The break angle calculated from the model showed good agreement with those calculated using field data. The break angle varied while the orebody width changed. A discrete element method was also used to analyze the hangingwall - caved rock - footwall interaction. The model showed that the caved rock constrains the movement of the hangingwall and footwall. Additionally, the model for the mine section Y1500 indicated that without the backfill the footwall will fail. The time-dependent behaviour of the hangingwall was analyzed using time- displacement curves obtained from surveying stations. Three different phases were found - regressive phase, steady state, and progressive phase. The rate of movement was estimated for the first two phases. Additionally, strain analysis was carried out using subsidence data from the hangingwall. The results indicated that critical values of tensile strain can be reached before visible cracks can be found on the surface. Moreover, large geological structures concentrate the strains, creating abnormal subsidence behaviour at the hangingwall. Godkänd; 2008; 20080505 (ysko)